Brain stimulation effects on serum BDNF, VEGF, and TNFα in treatment‐resistant psychiatric disorders. (25th April 2021) - Valiuliene, Giedre; Valiulis, Vladas; Dapsys, Kastytis; Vitkeviciene, Aida; Gerulskis, Giedrius; Navakauskiene, Ruta; Germanavicius, Arunas
Abstract: Resistance to pharmacological treatment poses a notable challenge for psychiatry. Such cases are usually treated with brain stimulation techniques, including repetitive transcranial magnetic stimulation (rTMS) and electroconvulsive therapy (ECT). Empirical evidence links treatment resistance to insufficient brain plasticity and chronic inflammation. Therefore, this study encompasses analysis of neurotrophic and inflammatory factors in psychiatric patients undergoing rTMS and ECT in order to refine the selection of patients and predict clinical outcomes. This study enrolled 25 drug‐resistant depressive patients undergoing rTMS and 31 drug‐resistant schizophrenia patients undergoing ECT. Clinical efficacy of brain stimulation therapies was gauged using MADRS and HAM‐D scales in the depression group and PANSS scale in the schizophrenia group. Blood‐derived BDNF, VEGF, and TNFα were analysed during the treatment course. For reference, 19 healthy control subjects were also enrolled. After statistical analysis, no significant differences were detected in BDNF, VEGF, and TNFα concentrations among healthy, depressive, and schizophrenic subject groups before the treatment. However, depressive patient treatment with rTMS has increased BDNF concentration, while schizophrenic patient treatment with ECT has lowered the concentration of TNFα. Our findings suggest that a lower initial TNFα concentration could be a marker for treatment success in depressed patients undergoing rTMS, whereas in schizophrenic patient group treated with ECT, a higher concentration of VEGF correlates to milder symptoms post‐treatment, especially in the negative scale. Abstract : Our study showed BDNF increase following rTMS course for depression patients and TNFα reduction after ECT for schizophrenia patients. However, from prognostic perspective, lower TNFα concentration predicted better depressive therapy response, while higher VEGF concentration correlated with milder schizophrenia symptoms after ECT course.